2022
DOI: 10.1007/s11663-022-02475-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology and Structural Evolution of Magnetite-Based Iron Ore Fines During the Oxidation

Abstract: The use of magnetite-based iron ore fines by means of fluidized bed technology has become a promising route to produce direct reduced iron. The significant influence of a prior oxidation treatment, which occurs in the preheating stage, on the subsequent fluidization and reduction behavior was observed in our previous study. As a result, it is important to investigate the oxidation of magnetite-based iron ore fines for an optimization of the proposed route. Three magnetite-based iron ore brands were analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
3
1
0
Order By: Relevance
“…Our previous study suggested tha the solid-state oxidation of magnetite to hematite during the cooling of the combusted particles resulted in linear patterns on the surface of PartOx particles [36]. Similar patterns were previously reported in the literature, which were rationalized by the oxidation of magnetite to hematite [47] and the associated outgrowth of hematite along preferred orientations [48]. During oxidation, outward iron cation diffusion is indeed favored compared with inward oxygen anion diffusion in the magnetite crystal structure [49].…”
Section: Influence Of Deep Pre-oxidationsupporting
confidence: 82%
See 1 more Smart Citation
“…Our previous study suggested tha the solid-state oxidation of magnetite to hematite during the cooling of the combusted particles resulted in linear patterns on the surface of PartOx particles [36]. Similar patterns were previously reported in the literature, which were rationalized by the oxidation of magnetite to hematite [47] and the associated outgrowth of hematite along preferred orientations [48]. During oxidation, outward iron cation diffusion is indeed favored compared with inward oxygen anion diffusion in the magnetite crystal structure [49].…”
Section: Influence Of Deep Pre-oxidationsupporting
confidence: 82%
“…Larger equiaxed grains are preferred at higher oxidation temperatures due to the improved ionic diffusion, which allows the system to decrease its total interface energy. The decrease in surface area during the oxidation process was also previously reported in the literature during oxidation at 1100 • C [48]. It was attributed to an activated sintering process at high temperatures, to decrease the internal energy of the system.…”
Section: Influence Of Deep Pre-oxidationsupporting
confidence: 80%
“…25,26 The microstructural analysis of the surface of CRJ, MSR, ISR, and ISR-ER OC particles was performed using FEG-SEM with EDX, as shown in Figure 4, as well as chemical mapping with the elemental chemical composition presented in Table 1. CRJ, ISR, and ISR-ER particles present more irregular structures and without definition in their shape; however, it can be seen that there are flatter faces forming pointed edges, as was also observed by Zheng et al 27 when studying the structural evolution and surface morphology of iron ores during the oxidation stage. The CRJ and ISR OCs revealed the presence of silica impurity particles widely spread on the surface; see Figure 4a,b.…”
Section: Screening Of Iron-based Materialssupporting
confidence: 72%
“…In comparison with the results obtained at lower temperatures, the intensity of the diffraction peaks for Fe 2 O 3 and TiO 2 exhibited a slight decrease at T oxi = 900 °C, which is due to the sintering phenomenon of vanadium titanomagnetite. 30 The XRD results indicated that the low-temperature (T oxi = 500 °C, T oxi = 700 °C) oxidation separates the Fe/Ti in vanadium titanomagnetite, while the high-temperature (T oxi = 900 °C) oxidation makes the separated hematite (Fe 2 O 3 ) and rutile (TiO 2 ) recombine and form pseudobrookite (Fe 2 TiO 5 ).…”
Section: Effect Of Oxidation Temperature (T Oxi ) Onmentioning
confidence: 99%